public perception of the plan of conversion of kerosene to LPG in urban districts bungus bungus west bay sackcloth desert - Ningsih, Nesvi Yulia; Ahmad, Ridwan; Nefilinda, Nefilinda (Pendidikan Geografi, 2013)
This study aims to describe in depth about public perception of Conversion Plan Fuel Kerosene to LPG Gas in the Village West district Bungus Bungus sackcloth Bay of Padang.This study uses qualitative research informants Bungus West Village is the community that would be expected to do the conversion of kerosene to LPG. Data collected by observation techniques ,interviewing , field recording and the active participation of investigators.The data collected were analyzed using the techniques of data reduction , data display and conclusion drawing and verification.Based on the results of the field study showed that : ( 1 ) the public perception of kerosene users stating that people prefer to use kerosene stoves because they have been accustomed , in the value of safer , easier, cheaper discovered and can be purchased per liter in retail diwarung and bases . for the use of LPG gas is considered more efficient , practical , environmentally friendly and used for cooking . ( 2 ) the perception of kerosene supplier stating that the plan konveri oil to gas will greatly affect their economies and businesses that they run so this will be stopped and can result in them being reduced income . ( 3 ) the perception of kerosene retailers stated that they were a little disappointed with the planned conversion of kerosene to LPG , because their income will be reduced and can not sell kerosene again .